The Chemistry and Kinetics of Polyethylene Pyrolysis: A Process to Produce Fuels and Chemicals. Issue 7 (27th February 2020) - Zhao, Dongting; Wang, Xianhua; Miller, James B.; Huber, George W.
Abstract: The annual global production of plastics reached 335 million metric tons in 2016. Most waste plastics are landfilled or enter the natural environment in an uncontrolled manner. Pyrolysis can convert waste plastics, such as polyethylene (PE), to smaller hydrocarbons that can be used as fuels or chemicals. In this work, pyrolysis of PE was studied by thermogravimetric analysis (TGA) and in a fluidized‐bed reactor. A kinetic model based on two parallel first‐order random‐scission steps was developed on the basis of the TGA results. PE was pyrolyzed in a fluidized‐bed reactor over the temperature range of 500–600 °C and at residence times of 12.4–20.4 s. The yield of gas‐phase products increased from 8.2 to 56.8 wt %, and the yield of liquid‐phase products decreased from 81.2 to 28.5 wt % as the temperature increased from 500 to 600 °C. Detailed analysis of the gas‐ and liquid‐phase products revealed their potential as precursors for production of fuels and chemicals. Gas‐phase products included hydrogen, C1 –C4 paraffins, C2 –C4 olefins, and 1, 3‐butadiene. The major liquid‐phase products were mono‐olefins and cycloalkanes/alkadienes with smaller amounts of n ‐paraffins, isoparaffins, and aromatics. The carbon‐number distribution of the fluidized‐bed pyrolysis products suggested contributions of nonrandom reactions of random‐scission fragments at low conversion. Abstract : Going up in flames : The pyrolysis of polyethylene waste plastic is studied by thermogravimetric analysis (TGA) and in a fluidized‐bed reactor. A kinetic model consisting of two parallel first‐order random scission steps is proposed on the basis of the TGA study. The gas‐ and liquid‐phase pyrolysis products from the fluidized‐bed reactor are potential precursors for the production of fuels and chemicals.